DESIGN OF E-LEARNING SYSTEM STMIK JAKARTA (STI&K) USING PHP - Arie Prihandhika (Jurnal Sistem Informasi, 2010)
In reality of course, some or most of the students STMIK Jakarta (STI&K) notyet capable of achieving individual competence required to follow the lessonsand apply them effectively advanced in solving everyday problems thatcontextual learning, if only during hours of face to face ongoing. This is not tomention plus the possibility of absenteeism of students and lecturers for somethings that can disrupt or reduce face-to-face lecture schedule of predetermined.Information and communication needs in a lecture that can be accessed anytimeand anywhere, is at the core of the problem.At this writing will explain how to design an application system by usingelectronic media in teaching and learning activities that are known by the terme- Learning to solve the problems above. The design of the application is ofcourse required an analysis of user needs, so as to realize the e-Learningsolutions are designed as an attractive, effective and preferred by users.